Tinjauan Yuridis Pemberian Hibah yang Dibatalkan Karena Melanggar Bagian Mutlak/Legitime Portie (Studi Putusan Mahkamah Agung Nomor 214 PK/Pdt/2017) - Priamsari, Ayu Dian; Sudarto, Sudarto (FOCUS, 2026)
Civil inheritance law under the Indonesian Civil Code (KUHPerdata) provides protection to heirs through the concept of compulsory share or legitime portie. This right ensures that legitimate heirs receive a certain portion of the deceased’s estate, even if a gift or will seeks to override their rights. This study aims to analyze the application of legitime portie in Indonesian inheritance law, with a focus on Supreme Court Decision Number 214 PK/Pdt/2017, which annulled a gift that violated the compulsory share. Using a normative approach and secondary data, this research demonstrates that the annulment of a gift that violates legitime portie is a legitimate and necessary step in ensuring justice and legal certainty for the rightful heirs. The study emphasizes that the protection of heirs' rights is essential for fairness in the inheritance process. Furthermore, the author suggests that testators should consult legal experts or notaries when drafting gifts or wills to prevent violations of legitimate heirs’ rights. This recommendation aims to avoid potential legal disputes and ensure that the distribution of the estate is fair and in accordance with the law. This research contributes to a deeper understanding of the protection of heirs' rights within the context of Indonesian inheritance law and highlights the importance of upholding justice in inheritance decisions.